Integral process of obtaining glycerol as a by-product of biodiesel production from castor oil - Romero, Leonel; Cortez, Ricardo; Sanchéz, Lizzmary; Piracoca, Marcela; Ayala, Lina; Becerra-Castro, Yeimy (Universidad Pedagógica y Tecnológica de Colombia - UPTC, 2012)
The biodiesel is obtained from about 10 years ago in Europe, and now that it has taken hold as fuel for diesel engines, it is expected a clear increase in the production of this class of fuels in a the near future. The biodiesel is derived from the transesterification reaction of castor oil with methanol, which is the main by-product the glycerol with an approximate content of 10%. Besides catalyst residuals, soaps, methanol traces, mono and diglycerides in small percentages are presented. This study proposes the separation, purification and characterization of the glycerol obtained from the transesterificación reaction of the castor oil, in order to be able to market it in the national or international market, so that it fulfills the standards of quality, which means getting a pure glycerol and the appropriate physico-chemical characteristics and techniques. The glycerin-methyl esters separation is carried out by decantation being obtained a percentage of around 70% glycerol. This percentage is subsequently increased through the purification process, using hydrochloric acid. Glycerol characterization was carried out by physicochemical and organoleptic tests. The purification process allowed us to obtain a glycerol with a percentage of purity close to 98%. It was also tested by comparison with theoretical data that remnants influenced in the physiochemical properties